1994
DOI: 10.1111/j.1600-051x.1994.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose response of chlorhexidine against plaque and comparison with triclosan

Abstract: The optimum dose of chlorhexidine delivered by mouthrinse, which balances efficacy against local side-effects, is generally considered to be in the region of 20 mg 2 x daily. Unfortunately, there have been few dose-response studies for chlorhexidine mouthrinses and for these, only limited details are published. The aims of this study were to determine the dose response of chlorhexidine to plaque inhibition and position a 0.1% triclosan rinse within this model. 28 subjects took part in this 7-treatment, double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
2
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 26 publications
6
77
2
6
Order By: Relevance
“…A 4-day dose-response study demonstrated a small but significant reduction in plaque for a 0.20% CHX mouthrinse compared to a 0.10% CHX mouthrinse [Jenkins et al, 1994]. When used as an adjunct to regular mechanical oral hygiene procedures during 4 weeks mouthrinses with 0.20% CHX reduced plaque accumulation slightly but not significantly better than 0.10% CHX mouthrinses [Flötra et al, 1972].…”
Section: Discussionmentioning
confidence: 99%
“…A 4-day dose-response study demonstrated a small but significant reduction in plaque for a 0.20% CHX mouthrinse compared to a 0.10% CHX mouthrinse [Jenkins et al, 1994]. When used as an adjunct to regular mechanical oral hygiene procedures during 4 weeks mouthrinses with 0.20% CHX reduced plaque accumulation slightly but not significantly better than 0.10% CHX mouthrinses [Flötra et al, 1972].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental gingivitis and dental plaque accumulation models are acknowledged as the best design to prove both plaque accumulation and gingival health effects of active components in mouthrinse preparations, as shown in numerous clinical studies (13,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of mechanical oral hygiene procedures, the 6-day (short-term) plaque re-growth study is conducted. Similarly, in several studies, a short-term plaque regrowth model was used to assess the chemotherapeutic plaque inhibitory activity of different formulations (1,8,9,13,18).…”
Section: Discussionmentioning
confidence: 99%
“…In order to further overcome any potential effects of the sequential crossover design of this study, the sequence of mouthwash usage was randomized so that 3 subjects used the test mouthwash first, 3 subjects used the control mouthwash first, and 4 subjects used no mouthwash at all first [28]. Overall, during the 8-week study period, oral health improved in both groups using the mouthwash [29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%